FACIES IDENTIFICATION AND DISTRIBUTION OF TALANGAKAR FORMATION, RHP FIELD, SOUTH SUMATRA - Hutama Putra, Rachmayudha
RHP Field is located in the South Sumatra Basin which administratively is located 40 km to the northwest of Palembang City as a part of Banyuasin Regency, South Sumatra Province. RHP field has been known as one of the oil fields in the South Sumatra Basin whose reservoir target was in the form of clastic sandstone in the Talangakar Formation. During its development, sandstone reservoirs in the Talangakar Formation are different from one well to another, and are not continuous so they need to be reviewed further. This study focused on the intervals of the Talangakar Formation for facies identification and distribution. The goal is to determine the character of reservoir distribution at RHP Field. This study involved 47 wells in which 9 of them had core description data and 5 of them had biostratigraphy analysis data. This study aims to specify the character of facies distribution in the Talangakar Formation by identifying facies from the integration of core description data, cuttings description data, and wireline log using a sequence stratigraphic method along with the guidance from the report of biostratigraphy analysis results at RHP Field in order to determine sequence markers and patterns. Furthermore, the results of facies identification produced an interpretation of the depositional environment which was then distributed using the thickness map data approach. Based on the analysis results, RHP field is divided into six zones with the oldest layer being called as zone one. Moreover, it has one deposition sequence pattern where the lower class limit is the sequence boundary one, while the upper class limit is the sequence boundary two. RHP field is also classified into six depositional environments, namely fluvial channel, tidal sand bar, mixflat, mudflat, and alluvial fan in which all of them are included in the estuarine deposit system. The distribution of the mudflat and mixflat depositional environment is increasingly expanding towards the younger sedimentary layer, which is zone six.